Pengaruh Lama Penyimpanan Urine pada Suhu Kamar terhadap Jumlah Leukosit Studi pada Penderita Diabetes Melitus - Yayuk Kustiningsih; Jujuk Anton Cahyono; Nur Rahmiati (Medical Laboratory Technology Journal, 2016)
Abstract: Examination of urine leukocyte count usually use urine samples during and urine examination is performed while still fresh because elements in the form of urine begins to break down within 2 hours. The purpose of this study was to determine the effect of storage time on the number of leukocytes urine checked immediately (0 hours) and were kept 30, 60, 90, 120, 150 and 180 minutes at room temperature. Types of Research true experiment to investigate the result of a treatment, research conducted on four samples of urine of patients with diabetes mellitus who meet several criteria, namely blood glucose levels> 200 mg / dl and urine amount leukositnya> 30 cells / mm3, calculated using the Improved Neubauer . The result showed a decrease in the number of stored urine leukocytes 30 minutes = 10%, 60 min = 25%, 90 min = 32%, 120 minutes = 39%, 150 minutes = 43%, and 180 minutes = 51%. Values obtained by linear regression test p = 0.034 (